Mechanistic Methodology for Airport Pavement Design with Engineering Fabrics. Volume 2. Advanced Concepts, Validation, and Criteria. - Majidzadeh,Kamran; Ilves,George J.; Kumar,V. R. (1986)
This report is Volume II of a two volume set dealing with the application of non-woven fabrics to rigid airport pavements to control and/or retard the development of reflection cracking of flexible overlays due to both thermal stresses and load-associated fatigue. This volume describes the development of a new viscoelastic analysis model for the analysis of thermal cracking that utilizes fundamental material properties and does not rely on phenomenological distress functions. The methods developed in this work as well as those presented in Phase I (Volume I), have been validated on one airport and four highway projects. The validation is described in this report and shows that the developed analysis models predict the reflection cracking phenomenon for all projects very well. This report also describes the laboratory evaluation of a fiber-asphalt SAMI layer that shows promise for use in reflection cracking control. Finally, specifications for material properties, testing procedures, and construction methods are presented.